Pengawasan Dewan Perwakilan Rakyat Daerah Dalam Mencegah Korupsi di Daerah - Greg Suripatty; Hendrik Salmon; Julista Mustamu (PAMALI: Pattimura Magister Law Review, 2023)
Introduction: Corrupt practices do not only occur in government administration at the center, but also in the regions.Purposes of the Research:  To analyze and formulate legal arguments regarding the form of DPRD supervision in preventing corruption in the administration of regional government.Methods of the Research: The method used in this research is normative legal research to answer the legal problem in question.Results of the Research: Research results show that the principle of DPRD supervision in the administration of regional government is to prevent violations or abuses committed by regional governments in implementing regional regulations and regional head regulations, laws and regulations related to the administration of regional government, and follow-up to audit results. Financial report by the Financial Audit Agency. Supervision is intended to be a means of creating checks and balances in the administration of government in the regions, but supervision must not result in reducing or undermining the values contained in the basic principles specified in statutory regulations, so that arbitrariness does not occur. If the DPRD carries out supervision effectively, it will have an impact on optimal regional government performance, including eradicating the practices of corruption, collusion and nepotism. The form of DPRD supervision in preventing corruption in the administration of regional government is not only in the form of political supervision, but also the role given to the DPRD to carry out technical supervision similar to supervision carried out in internal agencies to prevent corruption in the region.